(untitled) (Journal of Shaheed Suhrawardy Medical College, 2019)
Background: Ulcers and surgical wounds not healing well and expectedly are common problems among patients in countries like us. Ulcers may develop spontaneously or following a penetrating injury. wounds not healing well are common among poor, lower middle class and middle class people. Postsurgical non-healing wound or chronic discharging sinuses at the scar site are also common in that class of people. Suspecting malignancy or tuberculosis in these types of wounds we have sent wedge or excision biopsy for these ulcers in about 500 cases and found tuberculosis in 65 cases. In rest of the cases histopathology reports found as non- specific ulcers, Malignant melanoma, squamous or basal cell carcinoma, Verruca vulgaris. Objectives: To find out the relationship of tuberculosis with chronic or nonhealing ulcers. Methods: This is a prospective observational study conducted for patients coming to our chambers, OPD of a district general hospital and Shaheed Suhrawardy Medical College Hospital, Dhaka from July 2012 to June 2018. Results: Mean age of the study subjects were 28±2. Among the study subjects nonspecific ulcer or sinus tracts were found in 418 (83.6%), tuberculosis in 65 (13%), Malignant melanoma 7 (1.4%), Verruca vulgaris 5(1%), squamous cell carcinoma 3(0.6), basal cell carcinoma 2 (0.4%). Biopsy done only for very suspicious ulcers or wounds. Conclusion: With this very small sample size it is difficult to conclude regarding incidence of cutaneous involvement of extra pulmonary tuberculosis , but every clinician should think of it in case of suspicious non healing wounds, ulcers and prolonged discharge from a surgical incision site. J Shaheed Suhrawardy Med Coll, December 2018, Vol.10(2); 86-90